2020
DOI: 10.1002/fes3.243
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the source–sink relationships of zinc biofortification in wheat grains: A review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 181 publications
(382 reference statements)
3
21
0
Order By: Relevance
“…Our research showed that the application of Zn fertilizer (30 kg ZnSO4•7H2O ha -1 ) significantly increased grain yields/accumulation of N and K, and grain concentrations of Zn, N and K, but reduced Cu concentrations in wheat (Tables 2-3 and S2-S3). This is consistent with most previous studies on Zn [14,49,50], and consistent with Tao et al [48] on N. However, very few findings on the relationships between soil Zn application and grain accumulation of K or Cu were reported in wheat plants, which need a further verification. The simultaneous increase in grain concentrations of Zn and N could be explained by the interaction and co-localization of both within the grain, largely in the embryo and aleurone [51].…”
Section: Effects Of Soil Zn Fertilization On Grain Yield Traits and Nutrient Accumulation Of Wheatsupporting
confidence: 92%
See 4 more Smart Citations
“…Our research showed that the application of Zn fertilizer (30 kg ZnSO4•7H2O ha -1 ) significantly increased grain yields/accumulation of N and K, and grain concentrations of Zn, N and K, but reduced Cu concentrations in wheat (Tables 2-3 and S2-S3). This is consistent with most previous studies on Zn [14,49,50], and consistent with Tao et al [48] on N. However, very few findings on the relationships between soil Zn application and grain accumulation of K or Cu were reported in wheat plants, which need a further verification. The simultaneous increase in grain concentrations of Zn and N could be explained by the interaction and co-localization of both within the grain, largely in the embryo and aleurone [51].…”
Section: Effects Of Soil Zn Fertilization On Grain Yield Traits and Nutrient Accumulation Of Wheatsupporting
confidence: 92%
“…The contradiction between grain yield and nutritional quality in crop breeding and production has been observed in many previous studies [14,26]. Breeders usually struggle with the 8-25% yield reduction because of low phytate wheat lines used to improve grain Zn bioavailability [52,53].…”
Section: Cultivars Showing Higher Grain Yields Had Lower Grain Protein and Micronutrient Nutritional Qualitymentioning
confidence: 99%
See 3 more Smart Citations